2011
DOI: 10.2174/157488411794941304
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Treatment of Critically Ill Patients: The Latinuser Experience

Abstract: Tigecycline is the first of a new class of antibiotics named glycylcyclines and it was approved for the treatment of complicated intra-abdominal infections and skin and skin structure infections and community-acquired bacterial pneumonia. Notwithstanding this, the tigecycline's pharmacological and microbiological profile encourage physicians' use of the drug in other infections. The aim of this study was to characterize the indications type, pathogens, and outcomes of patients who were treated with tigecycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…This article presents a case series of pediatric patients who received tigecycline as salvage therapy for serious infections due to MDR/XDR bacteria after surgery, representing the largest experience of tigecycline administration in children after surgery in the English language literature. A favorable clinical response was seen in 86% of the patients, which is higher than in other studies (Bassetti et al, 2010;Curcio et al, 2011). This is especially remarkable given the fact that these patients had a greater disease severity and had failed previous treatment with highly potent broad-spectrum antimicrobials.…”
Section: Discussionmentioning
confidence: 56%
“…This article presents a case series of pediatric patients who received tigecycline as salvage therapy for serious infections due to MDR/XDR bacteria after surgery, representing the largest experience of tigecycline administration in children after surgery in the English language literature. A favorable clinical response was seen in 86% of the patients, which is higher than in other studies (Bassetti et al, 2010;Curcio et al, 2011). This is especially remarkable given the fact that these patients had a greater disease severity and had failed previous treatment with highly potent broad-spectrum antimicrobials.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, in a severe ICU population in Germany, tigecycline was also used mostly in combination (76 %), but the therapy frequently targeted Gram-positive cocci (including enterococci) possibly because of the high frequency of vancomycin-resistant strains. In Latin American countries, the tigecycline use in off-label indications appears to be important [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline has been used for many indications besides the FDA approved one. Although real life data about its use are limited, some studies involving intensive care patients have suggested promising results with tigecycline treatment (15,16). In this study, ventilatorassociated pneumonia in intensive care patients was one of the most common causes of tigecycline use.…”
Section: Discussionmentioning
confidence: 99%